Gorgeous & gruesome cakes for children : 30 original and fun designs kids will love - Brown, Debbie. frey50 (London : New Holland, 2010)
Demonstrates how to decorate cakes, from Cinderella's Glass Slipper to a ghastly Swamp Monster, includes recipes for a basic butter sponge cake and sugarpaste, with instructions and illustrations for creating novelty cakes.
Dotty dog -- Swamp monster -- Cloud castle -- Alien spaceship -- Ted in a box -- Pirate skull -- Trumpet tower -- Alien egg -- Frog prince -- Scary octopus -- Sea palace -- Shark! -- Acorn fairy -- Baby dinosaur -- Princess castle -- Spider trap -- Flower fairy -- The dungeon -- Ragdoll -- Troll house -- Glass slipper -- Hey monster! -- Midnight fairies -- Ugly bug -- Fairy wand -- Worms -- The butterfly ball -- Eyeballs -- Crowns and tiaras -- Bugs.
Includes index.
Keywords: Cake decorating; Birthday cakes; Cake decorating